2005
DOI: 10.1523/jneurosci.2270-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dendritic Arborization by the Phosphoinositide-3′-Kinase–Akt–Mammalian Target of Rapamycin Pathway

Abstract: The molecular mechanisms that determine the size and complexity of the neuronal dendritic tree are unclear. Here, we show that the phosphoinositide-3Ј kinase (PI3K)-Akt-mammalian target of rapamycin (mTOR) signaling pathway promotes the growth and branching of dendrites in cultured hippocampal neurons. Constitutively active mutants of Ras, PI3K, and Akt, or RNA interference (RNAi) knockdown of lipid phosphatase PTEN (phosphatase and tensin homolog deleted on chromosome Ten), induced growth and elaboration of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
478
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 534 publications
(519 citation statements)
references
References 87 publications
32
478
4
5
Order By: Relevance
“…The PI3K/AKT signaling pathway plays a central role in regulating cell growth, proliferation, and survival under physiologic and pathologic conditions. 34 In addition, in cultured hippocampal neurons, PI3K/AKT signaling has been shown to be involved in axonal sprouting, [22][23][24][25] which is an important mechanism underlying poststroke functional recovery. 17,18,35 Further, recent work has also shown that modulation of GSK-3 after stroke can enhance axonal outgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/AKT signaling pathway plays a central role in regulating cell growth, proliferation, and survival under physiologic and pathologic conditions. 34 In addition, in cultured hippocampal neurons, PI3K/AKT signaling has been shown to be involved in axonal sprouting, [22][23][24][25] which is an important mechanism underlying poststroke functional recovery. 17,18,35 Further, recent work has also shown that modulation of GSK-3 after stroke can enhance axonal outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and phosphorylation of PI3K/AKT signaling promotes neurite initiation, outgrowth, and growth cone stability, [22][23][24] as well as contributing to growth and branching of dendrites. 25 In addition, exercise has been shown to facilitate improvements in cognitive function via phosphorylation of AKT and CREB signaling and BNDF expression. [26][27][28] Based on these data, we hypothesized that blocking the combined BDNF and CX1837-induced phosphorylation of AKT using the pan-AKT inhibitor, GSK-690693, would impair the recovery trajectory.…”
Section: Combined Hydrogel Delivery Of Brain-derived Neurotrophic Facmentioning
confidence: 99%
“…Rapamycin has been previously used to define the mTORC1 contribution to neuronal polarization in neurons cultured longer than 3 days (Jaworski et al. 2005; Choi et al. 2008; Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the role of the mTORC1‐S6K pathway (Laplante and Sabatini 2009) in neuritic initiation we used the mTORC1 inhibitor rapamycin, which has been used in previous studies mostly to define the contribution of mTORC1 to neuronal polarization in neurons cultured for more than 3 days (Jaworski et al. 2005; Choi et al. 2008; Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation